Strategi Digitalisasi Transaksi Keuangan dalam Pengawasan dan Monitoring Kemitraan Universitas dan Bank Negara - Naila Mutia Hafidzah; Intan Dwi Noviana; Eva Hany Fanida; Melda Fadiyah Hidayat (CV. Ulil Albab Corp, 2026)
This study is motivated by the growing need for efficient, transparent, and accountable financial management systems in educational institutions through the use of digital technology. The objective of this study is to analyze strategies for the digitization of financial transactions in support of financial oversight and monitoring in partnerships between universities and state-owned banks. This study employs a descriptive-comparative qualitative approach, utilizing secondary data obtained through literature reviews and documentation, such as annual banking reports, payment system policy reports, and relevant institutional documents. The findings indicate that the digitization of financial transactions enhances operational efficiency, accelerates transaction processes, and supports real-time financial monitoring. Furthermore, digitalization also strengthens transparency and accountability in financial management and supports collaborative governance practices through cross-sector partnerships. However, the implementation of digitalization still faces challenges regarding human resource readiness and cybersecurity risks. Therefore, the digitalization of financial transactions is a crucial strategy for enhancing modern and sustainable financial governance.